(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2005)
The infinitesimal rigidity of hypersurfaces in R^n+1, n≥ 3, is considered. In section 1 we remind some definitions in the theory of the infinitesimal bendings (inf. b.). In section 2 we discuss the results in the papers [5 - 9]. In section 3 we consider our main result in the paper [10] and we give some geometric interpretations of the investigations in [10]. Finally we consider an example.